Active tuberculosis, sequelae and COVID-19 co-infection: first cohort of 49 cases. Issue 1 (9th July 2020) - Tadolini, Marina; Codecasa, Luigi Ruffo; García-García, José-María; Blanc, François-Xavier; Borisov, Sergey; Alffenaar, Jan-Willem; Andréjak, Claire; Bachez, Pierre; Bart, Pierre-Alexandre; Belilovski, Evgeny; Cardoso-Landivar, José; Centis, Rosella; et al.
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disease (COVID-19) pandemic has attracted interest because of its global rapid spread, clinical severity, high mortality rate and capacity to overwhelm healthcare systems [1, 2]. SARS-CoV-2 transmission occurs mainly through droplets, although surface contamination contributes and debate continues on aerosol transmission [3–5]. Diagnostic, treatment and outcome details of 49 COVID-19 patients with concurrent or previous tuberculosis from 8 countries show varied clinical profiles https://bit.ly/369ZGGu